Understanding the deterministic and probabilistic business cases for occupant based plug load management strategies in commercial office buildings. (1st April 2017) - Wang, S.; Kim, A.A.; Johnson, E.M.
Highlights: Deterministic and probabilistic business cases for plug load studies are proposed. The paper uses empirical data collected over an extended study period. Interventions failed to recover the expenses given uncertainties in cost estimates. Non-energy benefits can justify the investment from project manager's view. Abstract: Plug load monitoring and associated occupant behavior interventions can play a critical role in reducing commercial building energy consumption. This study investigates whether the reduction in building energy consumption justify the added cost of plug load monitoring and occupant energy saving interventions. The objective of this study is to conduct deterministic and probabilistic return-on-investment (ROI) analysis of instrumenting workspaces, monitoring plug load usage, and applying interventions to promote building energy reduction. The study uses the findings of actual occupant energy saving intervention investigations conducted with city and federal government offices in which the association between occupant energy savings interventions and energy use risk was evaluated. While the deterministic approach led to a positive net present value, the interventions failed to recapture the initial investment, and operational expenses given the uncertainties in the estimate of costs and energy use. The mean ten-year net present value was −$3914 at a 6% discount rate considering all U.S. states. From the project manager's perspective, other non-energy benefits can justify the additional resources.